Hubungan Penggunaan Gadget dengan Perkembangan Sosial dan Emosional Anak Usia Toddler - Nurul Jannah; Wahidah Wahidah; Ahmad Ahmad; Muhtar Muhtar (Poltekkes Kemenkes Mataram, 2023)
Gadget Currently, it has a huge influence on all groups, starting from parents, children and teenagers. Generally, children nowadays often use gadgets excessively. Excessive use of gadgets can affect social and emotional outcomes (Wahyuni, Siahaan et al. 2019). A phenomenon that often occurs is that parents often give gadget to his son for a reason gadget can accompany their children to play so that children become less interactive and prefer to be alone in their comfort zone with gadgets. This can cause children to become addicted gadget since early stage. Children's interest in electronic devices causes many problems related to mental, physical and social development, such as obesity, social isolation, stimulation of anger and violence due to games and others, and can even result in mental damage. The aim of this research is to determine the relationship between usage gadget with the social emotional development of children aged toddler in the Woha health center working area. The method used in correlation analytical research is a cross sectional approach. The sample in this study was parents who had children 1-3 years old, 234 respondents using purposive sampling technique. The instrument used in this research was a questionnaire. The research analysis used was the chi square test with a p value of 0.000 < 0.05, which means there is a relationship between gadget use and the social and emotional development of toddler-aged children in the Woha Community Health Center working area. Gadgets are just a means for children to play and search for information. Parents have a role in controlling every activity carried out by children, including use of them.gadget to prevent addiction and other impacts by limiting use gadget in children.